Stable Isotopic Evidence of Mixotrophy in Xylophagaids, Deep-Sea Wood-Boring Bivalves - Voight, Janet R.; Cooper, Jacob C.; Lee, Raymond W. (Frontiers in Marine Science, 2020)
Deep-sea wood-boring xylophagaid bivalves are thought to ingest only wood and to use nitrogen fixed by their symbiotic microbes. Reconsidering this assumption, we tested whether d13C and d15N isotopic values of ten species in four xylophagaid genera collected between 18 m and 4626 m depth suggest that some may use different trophic strategies. Isotopic signatures of six species were entirely consistent with predicted xylophagy, but four species, three members of the Xylophaga dorsalis clade and Abditoconus heterosiphon, had d15N signatures over 3.7‰, significantly higher than the value predicted for nitrogen fixed by bacteria. These species may supplement freshly fixed nitrogen with an alternate source, such as particulate organic material. Although the animals’ reduced palps and the lack of microbes in the gut of laboratory-maintained specimens were cited as arguing against filter feeding, the animals may filter feed opportunistically. Abditoconus heterosiphon was unique in having d13C signatures more negative than the wood into which they bored, inconsistent with cellulose consumption, and d15N values higher than predicted for nitrogen fixed by bacteria. We suggest that greater trophic diversity may exist among xylophagaids than has been expected. Ecological studies of wood-fall communities cannot assume that the entire community is sustained only by wood-bound energy. We attribute variation in d13C signatures among 42 specimens of X. s.l. zierenbergi from six collections, five at the same depth, to variation in the type of wood bored. Investigators beginning food web studies should sample xylophagaids and wood itself; if the deployment is large, repeated samples of the wood, closely matched to xylophagaids, may be necessarily to fully define the substrate’s stable isotopic signal.